Wind Tunnel Experiment on Impacts of Different Sand Barrier Layouts on Windbreak and Sand-fixing - Sun Jing; Wang Jun; Hong Junzhe; Jia Xiaojing; Zhang Shaoyun (Shuitu baochi tongbao)
[Objective] The influences of porous sand-fixing bricks layout on wind field characteristics, windbreak effect and sand-fixing were studied in order to provide a theoretical basis for the selection of new windbreak and sand-fixing materials. [Methods] The wind pressure distribution and the fluctuation of average wind pressure coefficient of a grid sand barrier and a gradient determinant sand barrier under wind conditions were explored by wind tunnel experiment. It was compared and analyzed emphatically for wind speed, windbreak efficiency, and sand accumulation for the two different types of sand barrier under sand storm. [Results] The average wind pressure coefficient inside the grid sand barrier was negative compared with the gradient determinant sand barrier, and the vortex generated by the internal wind circulation made it more stable under pressure. The average wind speed attenuation rate behind the grid sand barrier was higher than that behind the gradient determinant sand barrier. The windbreak efficiency first increased and then decreased with the increases of height along the height divection of sand barrier in barrier height. At 10 cm height, the windbreak efficiency of the grid sand barrier was 64.3%, which was 4.2% higher than that of gradient determinant sand barrier. The total sand deposition rates in the first row and the second row of the grid sand barrier were 1.14 and 1.66, respectively, times higher than that of the gradient determinant sand barrier. The amount of sand deposited behind the grid sand barrier and the deposition range behind the grid sand barrier were smaller than those values observed for the gradient determinant sand barrier. [Conclusion] The grid sand barrier had a significant attenuation effect on wind flow, and the sand resistance rate was higher than that of the gradient determinant sand barrier. Sand particles mainly settled inside the grid sand barrier, and its windbreak effect was better than observed for the gradient determinant sand barrier. The grid sand barrier was, therefore, judged to be the optimal sand barrier layout.